La migración venezolana y sus consecuencias desde la óptica coaccionada de los medios de comunicación (2021)
With the purpose of analyzing the responsibility of the media on the information and opinions they broadcast, theories of power and legal texts that establish the limits and obligations that fall on them are studied. From this analysis, it is found that Venezuelan migrants are victims of all kinds of discrimination, violating their fundamental rights, mainly human dignity.